2019
DOI: 10.32601/ejal.543787
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vocabulary vs. Syntactic Knowledge in L2 Reading Comprehension

Abstract: Research in literature reports the importance of L2 vocabulary and syntactic knowledge on the learners' reading comprehension. In this regard, the current study investigated the role of vocabulary knowledge that is disunited into depth and breadth dimensions and syntactic knowledge in the reading comprehension scores of an advanced cohort of English as a Foreign Language (EFL) learners. In particular, this study examined the relationship of vocabulary knowledge (with its two dimensions) and syntactic knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…However, the literature suggests that the role of grammar knowledge in receptive skills, namely listening and reading, is equivocal and inconclusive ( Buyl and Housen, 2015 ; Le Normand, 2018 ). Correlation-based and experimental studies have investigated the relationships between L2 vocabulary knowledge, L2 grammar knowledge, and L2 reading comprehension ( Henning et al, 1981 ; Nassaji and Geva, 1999 ; Khaldieh, 2001 ; Van Gelderen et al, 2003 , 2004 ; August, 2006 ; Shiotsu and Weir, 2007 ; Gottardo and Mueller, 2009 ; Guo and Roehrig, 2011 ; Morvay, 2012 ; Zhang, 2012 ; Nergis, 2013 ; Jeon and Yamashita, 2014 ; Kim and Cho, 2015 ; Lee, 2016 ; Susoy and Tanyer, 2019 ). However, these findings of these studies appear to be contradictory.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the literature suggests that the role of grammar knowledge in receptive skills, namely listening and reading, is equivocal and inconclusive ( Buyl and Housen, 2015 ; Le Normand, 2018 ). Correlation-based and experimental studies have investigated the relationships between L2 vocabulary knowledge, L2 grammar knowledge, and L2 reading comprehension ( Henning et al, 1981 ; Nassaji and Geva, 1999 ; Khaldieh, 2001 ; Van Gelderen et al, 2003 , 2004 ; August, 2006 ; Shiotsu and Weir, 2007 ; Gottardo and Mueller, 2009 ; Guo and Roehrig, 2011 ; Morvay, 2012 ; Zhang, 2012 ; Nergis, 2013 ; Jeon and Yamashita, 2014 ; Kim and Cho, 2015 ; Lee, 2016 ; Susoy and Tanyer, 2019 ). However, these findings of these studies appear to be contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…However, these findings of these studies appear to be contradictory. Some studies determined that L2 grammar knowledge can have a strong impact on L2 reading comprehension ( Henning et al, 1981 ; Van Gelderen et al, 2003 ; August, 2006 ; Shiotsu and Weir, 2007 ; Gottardo and Mueller, 2009 ; Guo and Roehrig, 2011 ; Nergis, 2013 ; Jeon and Yamashita, 2014 ; Kim and Cho, 2015 ), whereas other studies found that when the effects of vocabulary knowledge were partialed out, grammar knowledge played only a minor role in reading comprehension ( Nassaji and Geva, 1999 ; Khaldieh, 2001 ; Van Gelderen et al, 2004 ; Morvay, 2012 ; Zhang, 2012 ; Lee, 2016 ; Susoy and Tanyer, 2019 ). Moreover, issues such as research methodologies (e.g., whether the influence of vocabulary was controlled), sample sizes, and the English proficiency of the subjects suggested that the research findings were both inconclusive and difficult to interpret.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations